Space Economy: A Case Study on the Space Industry in the United Kingdom - Shinta Rahma Diana (DINASTI RESEARCH, 2021)
Activities in the space sector have evolved in which the role of the private sector has increased so that it can accelerate growth. Attention to space activities continues to increase, as seen from the space sector budget continues to increase and it is predicted that in 2040 the space economic will be in the range of 926 billion or 1.1 trillion. This is the total of the global space economy (activities in the global space economy value chain), one of which is a contribution from the British space industry. This study describes how the model of the space sector company was developed, and examples of companies in the UK that run a business in the space sector. It is expected that the business expansion model developed by companies engaged in the space sector with the large-size category can be found out. The study method used a descriptive method. The results show that the Space industry in the UK is developing in each group of the value chain, including in the last cluster of the space economy value chain (downstream sector) - industries that are included in the spinoff category, as well as development in the upstream sector. The company's expansion was demonstrated by the establishment of subsidiaries interested in investing in the British space sector. The space industry in the UK has grown tremendously and this is an economic driving sector that can contribute to revenue for the country and play a role in the global space economy value chain.